PENDAMPINGAN PERHITUNGAN HARGA POKOK PRODUKSI PADA USAHA MIKRO MAKANAN RINGAN DI DUSUN KWARASAN, NOGOTIRTO, GAMPING, SLEMAN - Hapsari, Yaning Tri; Marfuah, Hasti Hasanati; Kurniawanti, Kurniawanti; Samodro, Guntur; Dwinugroho, Theofilus Bayu (UNIVERSITAS PGRI MADIUN, 2023)
Abstract. Cost of Production (HPP) is an important element to assess the success (performance) of a trading or manufacturing company. Especially in determining the selling price and calculating the profit and loss of each product. Based on observations and interviews with “KREES” Banana Chips and Cheese Stick SME Owners, it is known that there are difficulties in recognizing what cost components must be calculated, thus causing difficulties in determining the optimal selling price to increase profits. The purpose of carrying out PKM activities is to provide assistance in calculating the Cost of Production (HPP) for UKM Banana Chips and Cheese Sticks